Ethnicity of Second-generation Japanese Indonesians in North Sumatra - ITO, Masatoshi (TALENTA, 2024)
The author has examined the ethnicity1 formation process of Japanese Indonesians in North Sumatra from various perspectives to determine their type of individuals. The diverse points of view are as follows: their common historical perspective as Japanese Indonesians, friendships between Japanese Indonesians from the time of the Issei2 to the present, the influence of Japanese culture in each family, their involvement with the Medan branch of the Yayasan Warga Persahabatan3, and the impact of working and living in Japan, among others. In the study of ethnicity among Japanese Indonesians, three factors are especially significant: blood ties, a sense of being the descendants of residual Japanese soldiers, and the Japanese influence from the Issei within the family. This paper is a compilation of the author’s research findings to date, with the addition of Nisei narratives to illustrate aspects of the Japanese Indonesians’ personality type.